2000
DOI: 10.1080/108556600110232
|View full text |Cite
|
Sign up to set email alerts
|

Roadgrading Community Culture: Why the Internet is so Dangerous to Real Democracy

Abstract: And I am not without hope. I knew a man who, in the age of chainsaws, went right on cutting his wood with a handsaw and axe. He was a healthier and a saner man than I am. I shall let his memory trouble my thoughts. 2 WENDELL BERRY ABSTRACT This article forwards an anarchist analysis of the internet as inherently degrading of local community and the possibility of real democracy emerging. The authors suggest that rampant virtuality, based on the eradication of time and space as functional communicative restra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As in the case of political participation and control, a separate part of the Internet literature has focused on the question of whether this new medium can change social behavior and relationships by enhancing the nature and frequency of social interaction, and the density of voluntary association. Some studies have found such positive effects (Gibson, Howard and Ward 2000;Boneva and Kraut 2002;Hampton and Wellman 2002;Quan-Haase and Wellman 2002;Kavanaugh and Patterson 2002), while others have concluded that the Internet tends to alienate individuals from one another and to increase social isolation (Hern and Chaulk 2000;Nie, Hillygus and Erbring 2002;Franzen 2000:435). In some cases, isolation and psychological stress were found to increase during the early stages of use (Kraut et al 1998), but not after the user had acquired a longer online experience .…”
Section: Notesmentioning
confidence: 99%
“…As in the case of political participation and control, a separate part of the Internet literature has focused on the question of whether this new medium can change social behavior and relationships by enhancing the nature and frequency of social interaction, and the density of voluntary association. Some studies have found such positive effects (Gibson, Howard and Ward 2000;Boneva and Kraut 2002;Hampton and Wellman 2002;Quan-Haase and Wellman 2002;Kavanaugh and Patterson 2002), while others have concluded that the Internet tends to alienate individuals from one another and to increase social isolation (Hern and Chaulk 2000;Nie, Hillygus and Erbring 2002;Franzen 2000:435). In some cases, isolation and psychological stress were found to increase during the early stages of use (Kraut et al 1998), but not after the user had acquired a longer online experience .…”
Section: Notesmentioning
confidence: 99%
“…The evolution of social media innovations has made it possible for people to connect over the internet (Kushin and Kitchener, 2009). Speaking on the impact of the internet, Hern and Chaulk (2000, p. 114) commented “the power of internet is that it allows individuals to transcend all the restraints that make local community time‐consuming, inefficient, limited, limiting and frustrating”. One such technological phenomenon, blogging, has risen dramatically in just a short time span.…”
Section: Review Of Literaturementioning
confidence: 99%